2014
DOI: 10.1016/j.steroids.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors alpha (ERα) and beta (ERβ): Subtype-selective ligands and clinical potential

Abstract: Estrogen receptors alpha (ERα) and beta (ERβ) are nuclear transcription factors that are involved in the regulation of many complex physiological processes in humans. Modulation of these receptors by prospective therapeutic agents is currently being considered for prevention and treatment of a wide variety of pathological conditions, such as, cancer, metabolic and cardiovascular diseases, neurodegeneration, inflammation, and osteoporosis. This review provides an overview and update of compounds that have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
399
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(445 citation statements)
references
References 163 publications
2
399
0
9
Order By: Relevance
“…This is especially true for steroid hormones 168,169 . Along these lines, a topic of great interest and translational potential is that of the interplay between their influence and epigenetic reprogramming of cells, with a well known interplay between ER and AR function and key histone and DNA modifying enzymes 13 , which can be targeted by a large battery of natural and synthetic compounds 170 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This is especially true for steroid hormones 168,169 . Along these lines, a topic of great interest and translational potential is that of the interplay between their influence and epigenetic reprogramming of cells, with a well known interplay between ER and AR function and key histone and DNA modifying enzymes 13 , which can be targeted by a large battery of natural and synthetic compounds 170 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Experimental studies have suggested that estradiol interferes with PPARG action and, consequently, with adipogenesis, by inhibiting adipocytic differentiation (7). Moreover, the relation between ER and inflammation has been described (5,8), with evidence that the regulation of pro-inflammatory cytokines expression by corticosteroids might be mediated by ERA and not by glucocorticoid receptor (GR) (9). These reports reinforce the hypothesis that ER, and particularly ERA, influences GO pathogenesis.…”
Section: Introductionmentioning
confidence: 68%
“…Although still controversial, the immunosuppressive role of estrogen in autoimmune diseases has been regarded as important (14). Thus, among the nuclear receptors possibly involved in GO, there are ERs, which have been associated with inflammatory processes, whether they are autoimmune or not (5,8). Although the mechanisms involved have not been elucidated yet, several factors seem to participate, such as, for instance, the IGF-1, which would exert an anti-inflammatory action mainly through ER, particularly ERA (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplements containing high levels of isoflavonoid phytoestrogens are now widely available [6]. Isoflavone usage has increased because of the correlations between the high soy isoflavone levels in Asian diets and the reduced incidence of coronary heart disease as well as prostate, colon and breast cancers which suggest a possible protective effect of isoflavones [7]. Other potential beneficial aspects of soy consumption include the prevention of osteoporosis as well as hormone replacement therapy in menopause [7].…”
Section: Introductionmentioning
confidence: 99%